2021
DOI: 10.1016/j.isci.2021.103478
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin-1 channel opening is critical for COVID-19 pathogenesis

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) rapidly rampaged worldwide, causing a pandemic of coronavirus disease (COVID -19), but the biology of SARS-CoV-2 remains under investigation. We demonstrate that both SARS-CoV-2 spike protein and human coronavirus 229E (hCoV-229E) or its purified S protein, one of the main viruses responsible for the common cold, induce the transient opening of Pannexin-1 (Panx-1) channels in human lung epithelial cells. However, the Panx-1 channel opening induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 195 publications
(201 reference statements)
1
37
0
Order By: Relevance
“…It should be noted that PxHC not only share many molecular and physiological characteristics with CxHC, but also contribute to the pathogenesis of inflammatory diseases. For instance, PxHC promote inflammasome activation, viral replication and infection (e.g., HIV and SARS-CoV-2) [ 166 , 167 , 168 ]. A combined blockade of CxHC and PxHC may prove to be more effective in the treatment of some inflammatory diseases than targeting either type of hemichannels.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that PxHC not only share many molecular and physiological characteristics with CxHC, but also contribute to the pathogenesis of inflammatory diseases. For instance, PxHC promote inflammasome activation, viral replication and infection (e.g., HIV and SARS-CoV-2) [ 166 , 167 , 168 ]. A combined blockade of CxHC and PxHC may prove to be more effective in the treatment of some inflammatory diseases than targeting either type of hemichannels.…”
Section: Discussionmentioning
confidence: 99%
“…Probenecid can modulate the expression of ACE2 [ 65 ], and targets the pannexin-1 gene, PANX1 [ 66 ]. PANX1 is an ATP release channel that facilitates the communication between T cells to inhibit the severity of airway inflammation [ 67 , 68 ]. PANX1 limits airway inflammation driven by type-2 CD4+ T-cell inflammatory responses, and probenecid is an inhibitor of PANX1 [ 69 ] that mediates the activation of caspase-1 and release of IL-1β induced by P2X7 receptor activation [ 70 ].…”
Section: Probenecid and Inflammationmentioning
confidence: 99%
“…In addition, Panx1 channel-mediated ATP release leads to an upregulation of Panx1 phosphorylation and of vascular cell adhesion molecule 1 and is, therefore, involved in the activation and migration of leukocytes [ 17 ]. Due to their contribution to inflammation and the link to viral infectious diseases, such as human immunodeficiency virus (HIV) infections and hepatitis C, it seems likely to assume that Panx1 channels can also play a role in COVID-19 [ 18 , 19 , 20 , 21 ]. Recently, it was found that the SARS-CoV-2 spike protein, a fusion protein essential in the induction of the infection, triggers prolonged Panx1 channel opening [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their contribution to inflammation and the link to viral infectious diseases, such as human immunodeficiency virus (HIV) infections and hepatitis C, it seems likely to assume that Panx1 channels can also play a role in COVID-19 [ 18 , 19 , 20 , 21 ]. Recently, it was found that the SARS-CoV-2 spike protein, a fusion protein essential in the induction of the infection, triggers prolonged Panx1 channel opening [ 18 ]. Furthermore, Panx1 mRNA and protein expression levels were shown to be elevated in samples of patients with a SARS-CoV2 infection, indicating a role of Panx1 channel opening in COVID-19 and suggesting Panx1 channels as potential drug targets [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation